Identifying preferred medium used in delivering effective Malaysian animated public service announcements (PSAs) among students / Dzaa Imma Abd Latiff, Mohd Anwar Fahmi Haridas Abdullah and Noor Ashmalia Mohd Asyraff - Abd Latiff, Dzaa Imma; Abdullah, Mohd Anwar Fahmi Haridas; Mohd Asyraff, Noor Ashmalia (Research Management Institute (RMI), 2011)
Animation is a simulation of movement created by displaying a series of pictures or frames, (i.e., cartoons) based on reality or fantasy which give impact to people's mind in terms of intellectuality, moral, and attitude. Public Service Announcements (PSAs) are designed to raise awareness, to change attitudes or to change ingrained behaviors. As technology develops, many PSAs apply animated characters in public health and safety campaigns. However, previous researchers were more interested to investigate the effect of PSA to students instead of the medium itself. Therefore, the researcher was interested to study whether the animated PSAs should be an effective tool in delivering messages to student in determining its effectiveness. Correlation analysis was used to study the relationship between preferred medium used, media interactivity and the effectiveness of animated PSAs among students. Findings showed that there was a strong positive relationship between Internet, Mobile phone and the effectiveness of Malaysian animated PSAs among students. This study is designed to determine the various functions of animation in public service announcements especially in understanding the needs of local context towards the government, consultants and media practices' parameters.